The effect of age on the clinical characteristics and innate immune cell function in the patients with abdominal sepsis - Lu, Jiaqi; Liu, Jingyuan; Zhu, Liuluan; Zhang, Yue; Li, Ang (Frontiers in Physiology, 2022)
Sepsis is a life-threatening dysregulated host response to infection that compromises organ health, and abdominal sepsis is a commonly presenting critical illness in intensive care units (ICU). In this study, we investigate the effect of age on clinical sepsis characteristics and innate immune cells (neutrophils and monocytes) functionality in abdominal sepsis patients. We recruited 32 patients with abdominal sepsis from the Beijing Ditan Hospital’s ICU from February 2021 to September 2021, and selected 18 healthy volunteers that were age- and sex-matched as controls for a prospective cohort study. Elderly abdominal sepsis patients had the following altered characteristics compared to controls: lower mean arterial pressure, monocytes percentage, and red blood cell volume distribution width (p<0.05); higher neutrophils percentage and neutrophils-to-lymphocytes ratio (p<0.05); significantly increased monocyte-produced reactive oxygen (p <0.05); increases neutrophilic secretion of TNF-α, as well as lower monocytic secretion of TNF-α (p <0.05); higher neutrophil percentage (which was significantly higher in peripheral blood than monocyte percentage). Elderly patients also had significantly increased phagocytic activity in their neutrophils and monocytes (p<0.05), significantly reduced neutrophils-produced reactive oxygen (p<0.001), and significantly increased TNF-α secretion by monocytes and neutrophils (p<0.05). We found that elderly patients have decreased immune cell function and increased release of cytokines compared to younger patients, suggesting individualized treatment plans targeting the elderly septic microenvironment could help prevent organ failure in elderly septic patients and improves patient survival.